Análise de risco da expansão da Área Livre de Pragas da mosca-das-frutas Anastrepha grandis (Macquart, 1846) (Diptera: Tephritidae) por modelagem preditiva de nicho MaxEnt - Maia Neto, João Egidio Ferreira (Universidade Federal Rural do Semi-Árido, 2021)
The pest free area (ALP) of the fruit fly Anastrepha grandis (Macquart, 1846) (Diptera: Tephritidae) has an important socioeconomic role for the semi-arid region of northeastern Brazil, so that the maintenance of this status must be preserved with the use of more varied control and monitoring techniques for pest insects. Understanding the ecological niche of this species and its responses to climatic factors provide an estimate of its distribution capacity and the possibility of its dispersal to control zones. The adhesion of new areas to the ALP validated by Ordinance No. 305 of May 12, 2021, may jeopardize its maintenance if this decision is not made with knowledge of the species' ability to adapt to that environment. Using the bioclimatic variables Bio1, Bio2, Bio3, Bio7, Bio12, Bio13, Bio17 and Bio19, in contrast to the coordinates of occurrence of A. grandis, a MaxEnt model was performed to identify its degree of adequacy in the Brazilian territory. The Linear and Quadratic features, and a regularization multiplier (rm) of 0.5, were selected as parameters. The modeling was carried out with 5000 interactions and 100 bootstrap replications using the Jackknife test to assess the impact of each variable and the designation of 30% of the occurrence points for training and the remainder for validation. The evaluation indicated a satisfactory AUC index of 0.915 and the Jackknife test indicated the variables Bio18, Bio1 and Bio12 as the three most impactful for the model. The results were projected on a map indicating areas of high suitability in the South, Southeast and Midwest regions, low environmental suitability for the North region and points of high suitability in the south of the Northeast, which are shown as entry points for pest dispersion in the region. The Northeast region, in general, showed low susceptibility to the presence of the species, confirming that the ALP is well placed in a region that is not suitable for the development of A. grandis, so that its expansion does not presently pose a risk for the introduction of the pest. Some isolated points with a high degree of suitability were identified in the state of Ceará and with the expansion in the state of Rio Grande do Norte, the territory of the ALP is approaching regions with risk above the general average
Keywords: Mosca das cucurbitáceas sul-americana; Biologia Evolutiva; Monitoramento de pragas; Modelagem computacional; South American cucurbit fruit fly; Evolutionary Biology; Pest monitoring; Computational modeling; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA